1991
DOI: 10.1111/j.1348-0421.1991.tb01615.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Aggregation by Strains of Enterococci

Abstract: The platelet aggregation capability of whole cells of Enterococcus faecalis, E. faecium and E. avium was tested. The optimum ratios of bacteria to platelets in E. faecali s (strain SMU-37), E. faecium (strain SMU-138) and E. avium (strain SMU-197) were 1.0, 1.2 and 2.0, respectively. During the platelet aggregation induced by the three strains of enterococci, 65-69% of total serotonin was released. The aggregation was totally inhibited by ethylenediaminetetraacetate (10 mM) and apyrase (1 mg/ml), while no effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Therefore there appears to be a difference between bacterial strains and species in what constitues their minimum plasma requirements for platelet aggregation. As mentioned earlier, we have shown that NCTC 7863 requires complement for platelet aggregation, as do zymosan (Zucker et al, 1974), certain tumour cells (Pulcinelli et al, 1995), certain monoclonal antibodies (Nomura et al, 1991) and enterococci (Usui et al, 1991), but at present we do not know what proportion of streptococcal strains require complement activation for platelet aggregation. Since aggregation of platelets by some organisms appears to differ in their requirement for complement, and perhaps for antibody, at least part of the mechanism leading up to platelet aggregation differs between strains, although probably all require fibrinogen interaction with GPIIb/IIIa as the final event.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore there appears to be a difference between bacterial strains and species in what constitues their minimum plasma requirements for platelet aggregation. As mentioned earlier, we have shown that NCTC 7863 requires complement for platelet aggregation, as do zymosan (Zucker et al, 1974), certain tumour cells (Pulcinelli et al, 1995), certain monoclonal antibodies (Nomura et al, 1991) and enterococci (Usui et al, 1991), but at present we do not know what proportion of streptococcal strains require complement activation for platelet aggregation. Since aggregation of platelets by some organisms appears to differ in their requirement for complement, and perhaps for antibody, at least part of the mechanism leading up to platelet aggregation differs between strains, although probably all require fibrinogen interaction with GPIIb/IIIa as the final event.…”
Section: Discussionmentioning
confidence: 74%
“…This functional redundancy suggests an interaction that is important for the bacteria. Indeed, various other pathogenic bacteria have also been shown to bind to and aggregate platelets, including Streptococcus sanguis (134) (133) (49), Enterococcus faecium, Enterococcus faecalis (139), and Streptococcus pyogenes (80).…”
Section: Antiplatelet Therapymentioning
confidence: 99%
“…A slower form of aggregation occurs for S. aureus through interactions with specific IgG and complement which induce platelet aggregation after a longer lagtime [6]. Aggregation of rabbit platelets in response to E. faecalis and Enterococcus faecium has been previously described, but the molecular mechanisms involved have not been determined [12]. [13].…”
Section: Introductionmentioning
confidence: 99%